2021
DOI: 10.1021/acs.energyfuels.1c03847
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Solution of the Mathematical Model for Constant Pressure Gas Desorption in a Coal Matrix

Abstract: An in-depth understanding of gas diffusion behavior in a coal matrix is essential for the prevention of gas hazards and the prediction of coalbed methane (CBM) recovery. There is still no consensus on the mechanism of coal matrix gas diffusion and further research is needed. In this paper, a mathematical model of coal matrix gas desorption and diffusion driven by the free-gas density gradient (FGDG) was proposed and developed, solved by finite-difference numerical methods, and validated with experiment data re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Gas generally exists in coal in the adsorption state and free state, and the gas in the two states is transformed into each other. The gas in the pore system of the coal matrix flows in the form of diffusion under the concentration gradient, 35 which conforms to Fick’s law where J m denotes the diffusion flux, m 3 /(m 2 s); D m is the diffusion coefficient, m 2 /s; and C m is the diffused gas content, m 3 /m 2 . Liu and Lin found that the diffusion coefficient D of gas in the matrix varies with the diffusion time, 36 and the functions of the dynamic diffusion coefficient and time are as follows …”
Section: Theoretical Model and Numerical Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…Gas generally exists in coal in the adsorption state and free state, and the gas in the two states is transformed into each other. The gas in the pore system of the coal matrix flows in the form of diffusion under the concentration gradient, 35 which conforms to Fick’s law where J m denotes the diffusion flux, m 3 /(m 2 s); D m is the diffusion coefficient, m 2 /s; and C m is the diffused gas content, m 3 /m 2 . Liu and Lin found that the diffusion coefficient D of gas in the matrix varies with the diffusion time, 36 and the functions of the dynamic diffusion coefficient and time are as follows …”
Section: Theoretical Model and Numerical Methodsmentioning
confidence: 84%
“…Gas generally exists in coal in the adsorption state and free state, and the gas in the two states is transformed into each other. The gas in the pore system of the coal matrix flows in the form of diffusion under the concentration gradient, 35 which conforms to Fick's law…”
Section: Theoretical Modelmentioning
confidence: 83%
“…Yi et al held that the diffusion coefficient declines with the decrease of the equilibrium pressure . Wu et al consider that the diffusion coefficient is unrelated to the gas pressure . In Figure (a), the diffusion coefficient substantially lies near 1.062 × 10 –10 m 2 /s.…”
Section: Discussionmentioning
confidence: 94%
“…Diffusion of gas is essentially driven by the pressure gradient of free gas, and the flow velocity is proportional to the pressure gradient but not directly related to the gas content. Qin et al derived the flow equation of diffusion driven by the density gradient of free gas: , J = D grad ρ g where J is the gas mass passing through unit coal particle per unit time, g/(cm 2 ·s) and ρ g refers to free gas density in coal particles, g/cm 2 .…”
Section: Model and Solution Of Diffusion Driven By The Pressure Gradi...mentioning
confidence: 99%
See 1 more Smart Citation